2015
DOI: 10.7314/apjcp.2015.16.3.1073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CXCR4 and CD133 Co-expression on the Prognosis of Patients with Stage II~III Colon Cancer

Abstract: Background: To explore the relationship between CXCR4, CD133 co-expression and clinicopathological features as well as prognosis of patients with phase Ⅱ~Ⅲ colon cancer. Materials and Methods: Forty-nine paraffin-embedded samples of tumor tissue and epithelial tissue adjacent to cancer were collected from patients with colon cancer undergoing radical surgery in Baotou Cancer Hospital from January, 2010 to June, 2011. CXCR4 and CD133 expression was detected using immunohistochemistry and its relationship with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Based on the selection criteria, a total of 37 studies published from 2008 to 2016 were eligible for the meta-analysis. [ 2 , 10 15 , 18 47 ] A total of 5397 CRC patients from China, Japan, South Korea, Italy, Germany, Australia, Spain, and Czech were enrolled. The study sample sizes ranged from 32 to 523 cases.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the selection criteria, a total of 37 studies published from 2008 to 2016 were eligible for the meta-analysis. [ 2 , 10 15 , 18 47 ] A total of 5397 CRC patients from China, Japan, South Korea, Italy, Germany, Australia, Spain, and Czech were enrolled. The study sample sizes ranged from 32 to 523 cases.…”
Section: Resultsmentioning
confidence: 99%
“…CXCR4, a seven-transmembrane G protein-coupled receptor, is a physiological receptor for stromal-derivedfactor-1 (19) which is highly expressed in various types of human tumors (20)(21)(22)(23)(24). A number of studies have demonstrated the vital role of CXCR4 in cancer cell survival, proliferation, invasion and metastasis, and that CXCR4 promotes EMT processes in various cancers (25)(26)(27)(28)(29), with CD133 + CXCR4 + cells showing a stronger invasiveness capacity (18,(30)(31)(32)(33).…”
Section: Cxcr4 Is Involved In Cd133-induced Emt In Non-small Cell Lunmentioning
confidence: 99%
“…The stromal cell-derived factor-1 (SDF-1/CXCR4) axis is involved in delivering signals related to chemotaxis, cell survival and/or proliferation, and thereby plays an important role in EMT and tumor invasiveness [ 43 , 44 ]. The co-expression of CXCR4 and CD133 in colon cancer may be associated with unfavorable prognosis [ 45 , 46 ]. Our data show that PRI-2191, PRI-1907 and PRI-1917 might be used to induce the loss of stem-like phenotype, as well as to decrease chemotactic and proliferative activity of colon cancer cells refractory to the cytoreductive treatment.…”
Section: Discussionmentioning
confidence: 99%